2019
DOI: 10.18203/2320-1770.ijrcog20191529
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcome following assisted reproductive technology in a tertiary care centre: a retrospective study

Abstract: Background: Infertility is a major issue and a source of social and psychological suffering for many couples. Introduction of assisted reproductive technology (ART) leads to great relief for couples nowadays.Methods: Present study was a retrospective study conducted at K.E.M hospital, a major tertiary care hospital after approval of the institutional ethics committee. A retrospective analysis of maternal and perinatal outcome of 30 cases of ART conception from the year 2014 to 2018 was done.Results: The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, for comparison, in their IVF group, significantly fewer neonates were in good condition based on the Apgar score at the fifth minute compared to non-IVF newborns (score 8-10: 325/334 vs. 304/305, respectively; P=0.023).27 Another retrospective study also found that 90.24% of neonates showed an Apgar score ≥7 at 5 minutes after birth. 28 The Apgar score at the fifth minute after birth and the change between the first and fifth minutes are useful references for assessing resuscitation response. If at the age of the fifth minute, the Apgar score can reach or more than seven, then peripartum hypoxia or ischemia is less likely to cause neonatal encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for comparison, in their IVF group, significantly fewer neonates were in good condition based on the Apgar score at the fifth minute compared to non-IVF newborns (score 8-10: 325/334 vs. 304/305, respectively; P=0.023).27 Another retrospective study also found that 90.24% of neonates showed an Apgar score ≥7 at 5 minutes after birth. 28 The Apgar score at the fifth minute after birth and the change between the first and fifth minutes are useful references for assessing resuscitation response. If at the age of the fifth minute, the Apgar score can reach or more than seven, then peripartum hypoxia or ischemia is less likely to cause neonatal encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Also, a study from India reported that 75.6% of infants born to IVFconceived pregnancies required treatment in NICU, with indications of prematurity and low birth weight. 28 A study observed preterm neonates in the NICU and compared IVF and non-IVF groups revealed that gestational age and birth weight were significantly lower in IVF group, while multiple births, cesarean section, and antenatal steroid administration were significantly higher. 7 However, the IVF group showed increased preterm delivery, but not preterm mortality, whereas preterm morbidity other than IVH did not differ in the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where 63.3 % women had singleton pregnancy and 36.67% had twin pregnancy. 11 In another study by Narayan et. al among 504 live born infants, almost half were twins i.e.…”
Section: Comparison Of Perinatal Outcomes By Birth Pluralitymentioning
confidence: 95%